ISLAMIC RELIGIOUS EDUCATION PEDAGOGIES: A SOCIOLOGICAL PERSPECTIVE ON SCHOOLS, MADRASAHS, AND ISLAMIC BOARDING SCHOOLS - Mustofa, Muhammad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This study aims to describe the importance of Islamic religious knowledge from a sociological perspective, serving as a guide for civilization. This article will explain the sociological overview within the components of Islamic education, the incorporation of Islamic education in the curriculum, and the patterns of Islamic religious education in pesantrens, madrasahs, and schools. The method used is a literature study using books or related articles as data sources. The results of this study are that the components of Islamic religious education consist of objectives, students, educators, curriculum, methods, environment, educational tools, and educational evaluation. The effort to include Islamic religious education in the curriculum began during the Dutch colonial era and continued during the era of Ki Hajar Dewantara when he served as the Minister of Education. The peak of Islamic religious education truly entering public schools occurred after the issuance of Law No. 2 of 1989 regarding the National Education System. Islamic religious education in schools, madrasahs, and pesantrens each has its own distinct character, where pesantrens have a deeply Islamic culture, then Islamic education was introduced into public schools as a basis for students to learn about Islam, while madrasahs attempt to merge the concepts applied in pesantrens and public schools.